2014
DOI: 10.5835/jecm.omu.30.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of warfarin overdose and efficacy of prothrombin complex concentrates

Abstract: IntroductionDrug overdose-related symptoms are an important part of emergency department (ED) admissions. Drug overdoserelated side effects are more common than suicidal drug intoxications. Drug overdosing is generally related to narrow therapeutic index of the relevant drug. A recent study revealed that drug side effect-related ED admissions comprised 3.6% of admissions in the elderly; 33.3% of these admissions were due to warfarin, digoxin and insulin (Budnitz et al., 2007). A previous study also revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In a study by Erdogan et al, [19] comorbidities in patients presenting with warfarin overdose found HT as the most common, followed by coronary artery disease, and congestive heart failure. Shireman et al [20] also reported HT as the most common comorbidity.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Erdogan et al, [19] comorbidities in patients presenting with warfarin overdose found HT as the most common, followed by coronary artery disease, and congestive heart failure. Shireman et al [20] also reported HT as the most common comorbidity.…”
Section: Discussionmentioning
confidence: 98%